Neo-contingency analysis of recruitment and selection: an Anglo-French study of high-tech and mid-tech vs. low-tech firms. (31st March 2005) - Ramirez, Jacobo
In recent years, there has been a considerable degree of interest in the notion of the different approaches to Human Resources Management (HRM) in diverse organisational settings. The objective of this article is to provide a new perspective on how technology, culture, and five recruitment and selection practices are approached through an Anglo-French sample of 163 firms. A neo-contingency approach has formulated the development of quantitative and qualitative data analysis. Differences are found between firms in the two countries; nonetheless, these differences do not argue that recruitment and selection policies and practices are universally applicable. Rather, technology intensity and cultural factors tend to shape the five HR practices studied. Thus, this article encourages more neo-contingency-type research in order to reach a better understanding of management studies in different organisational industrial and national settings.